(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Introduction: Modified radical mastectomy (MRM) is a standard surgical procedure for breast cancer, but postoperative wound drainage and seroma formation remain common complications that delay recovery. Topical tranexamic acid (TXA) has been proposed as a simple and safe method to reduce postoperative bleeding and related complications. Method: This Randomized Controlled Trial done at in tertiary care hospital, Nagpur. 60 patients undergoing MRM for biopsy-proven breast carcinoma were allocated into two groups (30 each). Group A received topical tranexamic acid (1 g), while Group B received an equal volume of normal saline before wound closure. Postoperative drain output, drain removal time, seroma formation, wound complications, and follow-up outcomes were compared. Result: Group A showed significantly lower drain output and drain removal occurred significantly earlier in Group A. Seroma formation was significantly lower in the TXA group while wound complications and two-week follow-up outcomes were comparable. Conclusion: Topical application of tranexamic acid during MRM effectively reduced postoperative wound drainage, facilitated earlier drain removal, and significantly decreased seroma formation without increasing postoperative complications.